Domestic Violence During the COVID-19 Pandemic – Analysis of Legal Solutions Adopted by Selected European Countries - Wilanowska, Monika (Medicine, Law & Society, 2021)
Domestic violence imposes a serious threat to the safety of both individuals and society in general. Experiencing domestic violence adversely affects the lives and health of victims in a particularly severe way. Reports provided by states and organisations demonstrate that domestic violence has increased during the COVID-19 pandemic. Governmental restrictions aimed at stopping the spread of the SARS-CoV-2 virus have had a negative impact on the victims of domestic violence, limiting their ability to benefit from the institutional support guaranteed by existing laws. An analysis of the domestic violence prevention solutions implemented by selected European countries during the COVID-19 pandemic leads to the conclusion that states were not prepared for the social impact of the introduced restrictions, such as an increase in domestic violence cases. Their measures mainly consist of establishing instructions for the functioning of certain institutions or guaranteeing the possibility of using the forms of assistance provided. The legal solutions that many European legislators have enacted are insufficient. No comprehensive strategies have been introduced to prevent this problem during the pandemic.